Modeling Dependence with Copulas: Are Real Estates and Tourism Associated? - Roengchai Tansuchat (2018)
© 2018, Springer International Publishing AG, part of Springer Nature. Several families of copulas are considered in this study to illustrate the correlation between real estate–particularly hospitality real estate investment trust- and the tourism sector. In essence, this study uses Elliptical copulas and Archimedean copulas, and more recent classes, like extreme value copulas and mixed copulas to conduct the experiment. Under a specific data set, it is revealed that the classical classes of copulas i.e., Elliptical and Archimedean, are selected most often for illustrating the dependency, followed by the extreme value class, particularly the Husler-Reiss copula. However, surprisingly, the mixed copula is not entirely preferable for this data set.